Idiopathic pre-capillary pulmonary hypertension in patients with end-stage kidney disease: effect of endothelin receptor antagonists - Nishimura, Masato (Clin Exp Nephrol, 2016)
BACKGROUND: We examined the prevalence, prognosis, and effect of endothelin receptor antagonists on survival in end-stage kidney disease patients with idiopathic pre-capillary pulmonary hypertension. METHODS: We investigated 1988 end-stage kidney disease patients in Toujinkai Hospital from January 1, 2001 to December 31, 2014. Pulmonary hypertension was screened by symptoms (dyspnea, hypotension, or near syncope) and echocardiography, and diagnosed by computed tomography with enhancement, pulmonary flow scintigraphy, and right heart catheterization. RESULTS: Fifteen patients (67 ± 11 years; 12 women and 3 men) were diagnosed as idiopathic pre-capillary pulmonary hypertension; mean pulmonary arterial pressure, pulmonary vascular resistance, or pulmonary artery wedge pressure were 55 ± 11 mmHg, 7.5 ± 2.9 Woods units, or 12 ± 2 mmHg, respectively. Of the 15 patients, 14 received hemodialysis, and 1 was in a pre-dialysis stage. Patients were followed through December 31, 2015, and 11 died of heart failure; their mean survival time was 26.4 ± 21.0 months. Endothelin receptor antagonists were used for 11 patients, and mean survival times were 57.3 ± 12.1 months in patients with endothelin receptor antagonists and 7.5 ± 2.1 months in those without. In the Kaplan–Meier analysis, heart failure death-free survival rates were higher in patients with endothelin receptor antagonists than in those without (P < 0.001); 100 versus 25 % at one year and 71 versus 0 % at 3 years. CONCLUSION: The prognosis of idiopathic pre-capillary pulmonary hypertension seems to be poor in end-stage kidney disease patients. Administration of endothelin receptor antagonists might improve the survival by inhibiting heart failure death. Registration of clinical trials This study was registered to the ClinicalTrials.gov (https://clinicaltrials.gov/): protocol identifier, NCT02743091.